Gender, crime and criminal justice - Fitz-Gibbon, Kate (Routledge, 2018)
chapter INTRODUCTION: WOMEN AND CRIME OR GENDER AND CRIME? -- part PART I THEORY -- chapter 1 CRIMINOLOGY, VICTIMOLOGY AND FEMINISM -- chapter 2 CRIMINOLOGY, VICTIMOLOGY AND MASCULINISM -- part PART II PRACTICE -- chapter 3 FEAR, RISK AND SECURITY -- chapter 4 GENDERING (SEXUAL) VIOLENCE -- part PART III POLICY -- chapter 5 POLICING GENDER-BASED VIOLENCE -- chapter 6 GENDER, LAW AND CRIMINAL JUSTICE POLICY.